1997
DOI: 10.1159/000264434
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Breathing Movements Are Associated with Changes in Compliance of the Left Ventricle

Abstract: We have tested the hypothesis that the limited fetal ventricular distensibility is not only an intrinsic cardiac characteristic but is also contributed to by the pressure exerted by the intrathoracic organs. To this purpose we have studied the diastolic cardiac function by Doppler velocimetry in 11 fetuses during fetal breathing and in 22 fetuses during apnea, controlling for gestational age at examination and heart rate. Inspiration was associated with a significant increase in left ventricular compliance, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In an earlier study, it was also found that septum primum maximal excursion is increased during fetal breathing, a finding that was related to an increase in left ventricular distensibility due to respiratory movements 24 .…”
Section: Resultsmentioning
confidence: 88%
“…In an earlier study, it was also found that septum primum maximal excursion is increased during fetal breathing, a finding that was related to an increase in left ventricular distensibility due to respiratory movements 24 .…”
Section: Resultsmentioning
confidence: 88%
“…We showed a significant reduction of pulmonary venous flow impedance, represented by the pulsatility index of the pulmonary vein, during fetal breathing movements. It is believed that, in apnea, the pressure of intrathoracic organs on the fetal heart, particularly as a result of nonexpanded lungs, limits ventricular distensibility 1 . Improvement of compliance and filling pressure reflects changes in venous return and end‐diastolic volume of the left ventricle, secondary to the fall of intrathoracic pressure during respiratory movements 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of fetal breathing has been used as a physiological model of increased ventricular compliance and relaxation, according to observations by Miyague et al 1 . Van Der Mooren et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another previous study has already demonstrated that, during fetal breathing, the excursion index of the septum primum is significantly increased; this finding was explained by an increase in left ventricular distensibility due to respiratory movements 7 . Therefore, excursion of the septum primum depends on multiple factors, and its correlation with the foramen ovale size has not been studied.…”
mentioning
confidence: 83%